Molecular characterization and differential effects of levofloxacin and ciprofloxacin on the potential for developing quinolone resistance among clinical Pseudomonas aeruginosa isolates - Kanafani, Zeina A.; Sleiman, Ahmad; Frem, Jim Abi; Doumat, George; Gharamti, Amal; El Hafi, Bassam; Doumith, Michel; AlGhoribi, Majed F.; Kanj, Souha S.; Araj, George F.; Matar, Ghassan M.; Abou Fayad, Antoine G. (Frontiers in Microbiology, 2023)
Background: Fluoroquinolones are some of the most used antimicrobial agents for the treatment of Pseudomonas aeruginosa. This study aimed at exploring the differential activity of ciprofloxacin and levofloxacin on the selection of resistance among P. aeruginosa isolates at our medical center.Methods: 233 P. aeruginosa clinical isolates were included in this study. Antimicrobial susceptibility testing (AST) was done using disk diffusion and broth microdilution assays. Random Amplification of Polymorphic DNA (RAPD) was done to determine the genetic relatedness between the isolates. Induction of resistance against ciprofloxacin and levofloxacin was done on 19 isolates.Fitness cost assay was done on the 38 induced mutants and their parental isolates. Finally, whole genome sequencing was done on 16 induced mutants and their 8 parental isolates.Results: AST results showed that aztreonam had the highest non-susceptibility. RAPD results identified 18 clusters. The 19 P. aeruginosa isolates that were induced against ciprofloxacin and levofloxacin yielded MICs ranging between 16 and 256 µg/mL. Levofloxacin required fewer passages in 10 isolates and the same number of passages in 9 isolates as compared to ciprofloxacin to reach their breakpoints. Fitness cost results showed that 12 and 10 induced mutants against ciprofloxacin and levofloxacin respectively had higher fitness cost when compared to their parentals isolates. Whole genome sequencing results showed that resistance to ciprofloxacin and levofloxacin in sequenced mutants were mainly associated with alterations in gyrA, gyrB and parC genes.Understanding resistance patterns and risk factors associated with infections is crucial to decrease the emerging threat of antimicrobial resistance.